A meta-analysis of effect of Traditional Chinese Medicine nursing technology in prevention of deep venous thrombosis after surgery for femoral neck fracture (中医护理技术预防股骨颈骨折术后深静脉血栓形成的Meta分析) - JIA Hui (贾慧); YANG Ge (杨鸽); HUANG Binqian (黄彬倩); PENG Hong (彭鸿); LI Chunbei (李春梅); WANG He (王贺) (Association of Integrative Nursing, 2023)
Objective To systematically review the effect of Traditional Chinese Medicine nursing technology in prevention of deep venous thrombosisafter surgery for femoral neck fracture. Methods The CNKI, Wanfang Data, VIP, SinoMed, PubMed, Embase, Cochrane Library and Web of Science were retrieved for random-controlled trails researches about the prevention of deep venous thrombosisafter surgery for femoral neck fracture. These databases were systematically searched from inception up to February 20, 2023. The meta-analysis was conducted using ReMan 5. 4software. Results A total of 12 articles with 942 patients finally were included. The results showed that the Traditional Chinese Medicine nursing technology was associated with a lower incidence of deep venous thrombosisafter surgery［OR=0. 18, 95%CI(0. 10, 0. 33), P＜0. 001］, lower degree of limb swelling［MD=-5. 22, 95%CI(-5. 76, -4. 68), P＜0. 001］ and higher degree of patient satisfaction［OR=7. 73, 95%CI(3. 83, 15. 61), P＜0. 001］ compared with routine intervention. In terms of coagulation indicators, there was no significant difference in APTT［MD=1. 20, 95%CI(-0. 29, 2. 69), P=0. 12］ and FIB［MD=-0. 41, 95%CI(-0. 90, 0. 09), P=0. 11］ between two groups, and there was a significant difference in PT［MD=1. 18, 95%CI(0. 62, 1. 73), P＜0. 001］between two groups. Conclusion Findings of the study showed an advantage of Traditional Chinese Medicine nursing technology in prevention of deep venous thrombosisafter surgery for femoral neck fracture. More high-quality studies with larger sample size are needed to verify the effect of intervention. (目的 系统评价中医护理预防股骨颈骨折术后深静脉血栓形成的效果。方法 计算机检索知网、万方、维普、中国生物医学数据库, PubMed、Embase、Cochrane Library、Web of Science核心数据库有关中医护理预防股骨颈骨折患者术后深静脉血栓形成的临床随机对照研究, 检索时间为从建库至2023年2月20日。采用ReMan 5. 4进行Meta分析。结果 最终纳入12篇文献研究, 共942例患者。Meta分析结果显示: 实验组(中医护理)在术后深静脉血栓的发生率［OR=0. 18, 95%CI(0. 10, 0. 33), P＜0. 001］、术后患肢肿胀程度［MD=-5. 22, 95%CI(-5. 76, -4. 68), P＜0. 001］, 患者满意度［OR=7. 73, 95%CI(3. 83, 15. 61), P＜0. 001］均优于对照组(常规护理); 凝血指标中APTT［MD=1. 20 , 95%CI(-0. 29, 2. 69), P=0. 12］, FIB［MD=-0. 41, 95%CI(-0. 90, 0. 09), P=0. 11］显示两组差异无统计学意义, 而PT［MD=1. 18, 95%CI(0. 62, 1. 73), P＜0. 001］显示两组差异有统计学意义。结论 在预防股骨颈骨折患者术后深静脉血栓中中医护理更有优势。受纳入研究的文献和质量的限制, 上述结论需要更多大样本、高质量的研究予以验证。)